Narrative Review: The Influence of Service Quality and Price on Pharmacy Patient Loyalty - Amna, Shily Rahmatika; Wiedyaningsih, Chairun; Ardiningtyas, Bondan (Majalah Farmaseutik, 2025)
A total of 30,199 retail pharmaceutical services were recorded in Indonesia in 2022, distributed across the country. The significant number of retail pharmacies intensifies competition within the sector. To compete effectively, retail pharmacies must gain and retain customer loyalty. It is widely recognized that service quality and price are key determinants of customer loyalty in the pharmacy sector. Notably, delivering high-quality services requires substantial financial investment. On the other hand, reducing prices to gain a competitive advantage may risk the company’s financial stability. This study aims to examine the comparative impact of service quality and price on customer loyalty in the pharmacy context. A narrative review methodology was employed, using the ScienceDirect, Summon, ProQuest, and Google Scholar databases to gather relevant literature. A total of 10 articles were analysed, examining the influence of service quality versus price on loyalty in pharmacies. Of these, eight articles concluded that service quality had a greater impact on customer loyalty, while two suggested that service quality and price had an equivalent influence. The findings of this study indicate that service quality has a more significant impact on customer loyalty in pharmacies.